SEJARAH PERKEMBANGAN MAZHAB NAHWU ARAB (SEBUAH TINJAUAN HISTORIS) - Ihsanudin . (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2017)
This paper describes the history of development of Arab syntax. In the classical Islamic vocabulary of Arabic syntax (famous among academic and non-academic)